Thiamethoxam-Loaded Ethyl Cellulose Microspheres for Extending the Efficacy Duration and Reducing the Toxicity on the Growth of Maize (Zea mays L.) - Xu, Peng (Langmuir : the ACS journal of surfaces and colloids, 2024)
Thiamethoxam has been widely used in agriculture due to its excellent insecticidal activity. However, thiamethoxam is prone to loss during practical applications, especially in soil application, which seriously reduces its performance. In this work, thiamethoxam is loaded in ethyl cellulose microspheres to solve this issue, and the thiamethoxam-loaded ethyl cellulose microspheres (thiamethoxam/EC) are facilely and effectively fabricated by emulsified solvent volatilization. The exceptional embedding capacity of thiamethoxam/EC was elucidated through a systematic investigation of its controlled release and antiphotolysis properties. The encapsulation efficiency of thiamethoxam/EC was found to be ∼70.36%. Even after 130 h in a phosphate-buffered saline solution, the release of thiamethoxam from the thiamethoxam/EC complex continued, with a cumulative release of ∼52.38%. In contrast, the cumulative release of thiamethoxam/EC in soil after being flushed with 580 mL of water was a mere 14.74%, significantly lower than the value of 42.73% observed for unencapsulated thiamethoxam at the same volume. Additionally, thiamethoxam/EC demonstrated benign biocompatibility with Escherichia coli and maize (Zea mays L.) seedlings. The ultraviolet resistance of thiamethoxam in the thiamethoxam/EC formulation was nearly 3 times greater than that of uncoated thiamethoxam, and the insecticidal efficacy against Mythimna separata improved by 11.46% at a low concentration of 1 mg/L after a 10 day incubation in a greenhouse. The microspheroidization process not only extended the efficacy duration of fluazinam on target crops but also contributed to the sustainable use of pesticides and environmental protection